2009
DOI: 10.1117/12.835880
|View full text |Cite
|
Sign up to set email alerts
|

Latest results and computing performance of the ePLACE data preparation tool

Abstract: At the EMLC 2009 in Dresden the data preparation package ePLACE was already presented. This package has been used for quite different applications covering mask write, direct write and special applications. In this paper we will disclose results achieved when using the ePLACE package for processing of layout data of immediate interest. During the evaluation phase of the new solution we could benefit from broad experience we collected over many years with the fracture performance of the MGS software, which is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thanks to these software tools, it is possible to determine the exact number of shots to be exposed. Based on this and as described in [4] , it is possible to simulate the write time in taking into account the resist sensitivity, the beam current density and, the PEC. For all layouts described in chapter 3 the corresponding values were determined.…”
Section: Comparison Of Shot Counts and Write Timesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to these software tools, it is possible to determine the exact number of shots to be exposed. Based on this and as described in [4] , it is possible to simulate the write time in taking into account the resist sensitivity, the beam current density and, the PEC. For all layouts described in chapter 3 the corresponding values were determined.…”
Section: Comparison Of Shot Counts and Write Timesmentioning
confidence: 99%
“…A comprehensive layout data preparation package including proximity effect correction (PEC) is provided by EQUIcon / Vistec and available for all Vistec shaped beam writers as well as for the new MSB generation [3] , [4] . Thanks to these software tools, it is possible to determine the exact number of shots to be exposed.…”
Section: Comparison Of Shot Counts and Write Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies we have shown by means of the ePLACE simulation feature [6,7] that the geometrically induced dose correction method provides a possibility to significantly enhance the dose distribution contrast and DST [8]. To demonstrate the achievable improvements, we have performed test exposures.…”
Section: Introductionmentioning
confidence: 96%